2017
DOI: 10.1088/1757-899x/176/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

TiO2Nanorods Preparation from Titanyl Sulphate Produced by Dissolution of Ilmenite

Abstract: Abstract. One-dimensional titanium oxides (TiO 2 ) nanorods have substantial applications in photocatalytic, nanoelectronic, and photoelectrochemical solar cells. These applications require large quantities of materials and a production technique suitable for future industry fabrication. We demonstrate here a new method of TiO 2 nanorods production from ilmenite sands (FeTiO 3 ). In this process, the roasted ilmenite sand was separated from the iron content and dissolved in the sulphuric acid solution. Separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…the gases from the reactions are exhausted in the synthesis system, as well as the water contained, in the form of steam and conducted to a gas scrubber system. The reaction is proposed below in 2 reactional steps (Wahyuningsih, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…the gases from the reactions are exhausted in the synthesis system, as well as the water contained, in the form of steam and conducted to a gas scrubber system. The reaction is proposed below in 2 reactional steps (Wahyuningsih, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Ilmenite obtained from Bangka, Indonesia was subjected to a more elaborate digestion procedure by Refs. [44,[64][65][66]. Ilmenite was preoxidized in open air for 6 h at temperatures ranging from 400 to 1100 °C.…”
Section: Leaching Using Hydrochloric Acid and Sulfuric Acidmentioning
confidence: 99%
“…When Na 2 S is added to ilmenite before roasting, Upon treatment with H 2 SO 4 (3, 3.5, 4.5, 6 and 9 M) the following reactions may occur and it was found that the ilmenite was more soluble in 6 M H 2 SO 4 . Fe 2+ and Fe 3+ ions are complexed with KSCN to prevent the contamination of the intermediate TiO(OH) 2 formed during the hydrolysis-condensation process of titanyl sulfate to produce TiO 2 as the final product [44,[64][65][66],…”
Section: Leaching Using Hydrochloric Acid and Sulfuric Acidmentioning
confidence: 99%